HBR's 10 Must Reads on Organizational Resilience (with bonus article ""Organizational Grit"" by Thomas H. Lee and Angela L. Duckworth). - Christensen, Clayton M.; Duckworth, Angela L.; Hamel, Gary.; Martin, Roger L.; Harvard Business Review (: Harvard Business Review Press, 2020)
Build resilience in your company to weather the greatest crises. If you read nothing else on organizational resilience, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help your company prepare for and overcome disruption, social upheaval, and disaster. This book will inspire you to: -Reposition your core business while launching a separate, disruptive business -Build the ability to continually anticipate and adjust to emerging trends -Prepare for the business implications of climate change -Learn about the risks of hyperefficient businesses -Develop organizational grit -Rebound from a recession faster than your competitors -Lead your company through any kind of crisis This collection of articles includes "How Resilience Works" by Diane Coutu; "The Quest for Resilience" by Gary Hamel and Liisa Valikangas; "Disruptive Technologies: Catching the Wave" by Joseph L. Bower and Clayton M. Christensen; "Organizational Grit" by Thomas H. Lee and Angela L. Duckworth; "Leading in Times of Trauma" by Jane E. Dutton, Peter J. Frost, Monica C. Worline, Jacoba M. Lilius, and Jason M. Kanov; "Learning from the Future" by J. Peter Scoblic; "Leading a New Era of Climate Action" by Andrew Winston; "The High Price of Efficiency" by Roger L. Martin; "Reigniting Growth" by Chris Zook and James Allen; "Global Supply Chains in a Post-Pandemic World" by Willy C. Shih; and "Roaring Out of Recession" by Ranjay Gulati, Nitin Nohria, and Franz Wohlgezogen. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sor
Intro -- Contents -- Ch. 1: How Resilience Works -- Ch. 2: The Quest for Resilience -- Ch. 3: Disruptive Technologies -- Ch. 4: Organizational Grit -- Ch 5: Leading in Times of Trauma -- Ch 6: Learning from the Future -- Ch 7: Leading a New Era of Climate Change -- Ch 8: The High Price of Efficiency -- Ch 9: Reigniting Growth -- Ch 10: Global Supply Chains in a Post-Pandemic World -- Ch 11: Roaring Out of Recession -- About the Contributors -- Index
Master record variable field(s) change: 050, 082
Keywords: Management; Leadership; Business; BUSINESS & ECONOMICS / Management; elektronické knihy; electronic books